Design of Single Degree of an Intersecting Line Translational Mechanism - Lin Hao; Shi Zhixin; Luo Yufeng; Ye Meiyan (Jixie chuandong)
Based on the intrinsic geometry, a new type of mechanism with single degree of freedom is designed which can translate along the intersecting line. According to the theory of azimuth feature set, the degree of freedom of the mechanism is calculated and its kinematics are analyzed. A coordinate system is established to solve the forward and inverse position solutions of the mechanism and it is verified. Based on the schematic diagram of the mechanism, a three-dimensional model is established with a specific dimension parameter, and the kinematics simulation is carried out in Recurdyn. The output characteristics of the terminal running trajectory are analyzed, and the feasibility of the mechanism is verified.